Subacute infective endocarditis presenting with an isolated splenic infarction - Maen MHD Baroudi (17746734) (2023)
Background Subacute endocarditis usually presents over a period of weeks or months. Symptoms usually include low grade fever, and generalized symptoms of malaise, anorexia, weight loss. Here we present a case of subacute endocarditis presenting solely as acute left hypochondrial pain, which was found to be splenic infarct. Typical symptoms of subacute endocarditis were absent in our patient. Case report A 48-year-old Yemeni gentleman presented to the emergency department with acute and severe left hypochondrial abdominal pain for a few hours. Blood investigations revealed normal blood count differential, renal, liver function, and electrolyte levels. CT abdomen with contrast showed large focal wedge-shaped splenic lesion representing splenic infarct. Initial workup was negative for an underlying etiology. TEE showed a spherical mobile mass attached to the aortic valve with moderate to severe aortic regurgitation. Subsequently, 3 sets of blood cultures were sent and revealed growth of streptococcus viridians in all bottles. The patient received IV antibiotics as a treatment of endocarditis. Conclusion This case highlights how subacute endocarditis presented as splenic infarction, with the absence of the typical infectious symptoms. In case of splenic infarction with unclear source or etiology, it is reasonable to investigate thoroughly for infective endocarditis preferably with TEE. Other Information Published in: IDCases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.idcr.2023.e01752